2012
DOI: 10.1590/s1517-83822012000300005
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of killer Candida glabrata clinical isolates

Abstract: In this work we characterized the occurrence of killer activity in 64 Candida glabrata clinical isolates under different conditions. We found that only 6.25 % of the clinical isolates tested were positive for killer activity against a Saccharomyces cerevisiae W303 sensitive strain. Sensitivity of killer activity to different values of pH and temperatures was analyzed. We found that the killer activity presented by all isolates was resistant to every pH and temperature tested, although optimal activity was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…These killer toxins exhibit variations in their inhibition spectrum, mechanism of action, molecular size, optimum pH and temperature, and they have been described in more than 20 genera of yeast from both the ascomycetes and basidiomycetes phyla (Golubev, 1998), from either clinical or natural sources (Souza Cabral et al, 2009;Arroyo-Helguera et al, 2012). Reports from Magliani et al (2004) and Polonelli et al (2003) have shown that killer toxins pose an interesting strategy for the development of new antifungal treatments that could overcome antifungal resistance due to the evolutionary origin of these interactions.…”
Section: Introductionmentioning
confidence: 99%
“…These killer toxins exhibit variations in their inhibition spectrum, mechanism of action, molecular size, optimum pH and temperature, and they have been described in more than 20 genera of yeast from both the ascomycetes and basidiomycetes phyla (Golubev, 1998), from either clinical or natural sources (Souza Cabral et al, 2009;Arroyo-Helguera et al, 2012). Reports from Magliani et al (2004) and Polonelli et al (2003) have shown that killer toxins pose an interesting strategy for the development of new antifungal treatments that could overcome antifungal resistance due to the evolutionary origin of these interactions.…”
Section: Introductionmentioning
confidence: 99%